A magnetometer-based method for in-situ syncing of wearable inertial measurement units - Gilbert, Thomas J.; Lin, Zexiao; Day, Sally; Hamilton, Antonia F. de C.; Ward, Jamie A. (Frontiers in Computer Science, 2024)
This paper presents a novel method to synchronise multiple wireless inertial measurement unit sensors (IMU) using their onboard magnetometers. The basic method uses an external electromagnetic pulse to create a known event measured by the magnetometer of multiple IMUs and in turn uses this to synchronise the devices. An initial evaluation using 4 commercial IMUs reveals a maximum error of 40ms per hour as limited by a 25 Hz sample rate. Building on this we introduce a novel method to improve synchronisation beyond the limitations imposed by the sample rate and evaluate this in a further study using 8 IMUs. We show that a sequence of electromagnetic pulses, in total lasting less than 3-seconds, can reduce the maximum synchronisation error to 8ms (for 25 Hz sample rate, and accounting for the transient response time of the magnetic field generator). An advantage of this method is that it can be applied to several devices, either simultaneously or individually, without the need to remove them from the context in which they are being used. This makes the approach particularly suited to synchronising multi-person on-body sensors while they are being worn.